Post-Decortication Effectiveness of Single-Chest Tube vs. Double-Chest Tube Placement - Mahek, Lubna; Aziz, Usama; Nayyer, Sajid; Rehman, Wajeeh Ur; Talat, Nabila (Biological and Clinical Sciences Research Journal, 2025)
The use of chest tube drainage following decortication is standard practice to ensure proper lung re-expansion and fluid evacuation. However, the optimal number of chest tubes required remains controversial, with limited evidence comparing single versus double tube placement. Objectives: To compare the effectiveness of single versus double chest tube placement in terms of post-operative pain, drainage characteristics, hospital stay, and complications following open decortication for organized empyema. Study Design & Setting: A randomized controlled trial conducted at Paediatric Surgery Unit 1, the Children’s Hospital, and the University of Child Health Sciences, Lahore, from February 2024 to July 2024. Methodology: A total of 150 patients with stage III empyema undergoing open decortication were randomly assigned into two equal groups: Group A received a single chest tube, and Group B received two chest tubes. Pain was assessed using the Visual Analog Scale (VAS) at 24, 48, and 72 hours. Other outcomes measured included chest tube duration, drainage volume, hospital stay, and postoperative complications. Data were analyzed using SPSS version 25.0, and p-values < 0.05 were considered statistically significant. Results: Group A experienced significantly lower VAS scores at 24, 48, and 72 hours (p < 0.001), shorter chest tube duration (p < 0.001), and reduced hospital stay (p < 0.001) compared to Group B. No statistically significant differences were observed in complication rates between the two groups. Conclusion: Single chest tube placement is effective and associated with better post-operative outcomes without increasing complications, suggesting it may be a preferable option after decortication.